2015
DOI: 10.1523/jneurosci.2043-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spine Loss in Primary Somatosensory Cortex during Trace Eyeblink Conditioning

Abstract: Classical conditioning that involves mnemonic processing, that is, a "trace" period between conditioned and unconditioned stimulus, requires awareness of the association to be formed and is considered a simple model paradigm for declarative learning. Barrel cortex, the whisker representation of primary somatosensory cortex, is required for the learning of a tactile variant of trace eyeblink conditioning (TTEBC) and undergoes distinct map plasticity during learning. To investigate the cellular mechanism underpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
6
18
0
Order By: Relevance
“…Thus, in our work, we have found different patterns of eyelid closing for delay and trace conditioning paradigms, although the shapes of those CRs were similar in WT and Lurcher mice. That shape was almost identical to those well described before in mice for delay 15 and trace 46 , 47 conditioning paradigms at early stages of the conditioning, when the position of the eyelid was recorded with technical procedures like the ones used here. Similar results for CR profiles were reported years ago in behaving cats 39 .…”
Section: Discussionsupporting
confidence: 77%
“…Thus, in our work, we have found different patterns of eyelid closing for delay and trace conditioning paradigms, although the shapes of those CRs were similar in WT and Lurcher mice. That shape was almost identical to those well described before in mice for delay 15 and trace 46 , 47 conditioning paradigms at early stages of the conditioning, when the position of the eyelid was recorded with technical procedures like the ones used here. Similar results for CR profiles were reported years ago in behaving cats 39 .…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, recent studies have reported modified EBC training procedures in which the mice were head-fixed on a wheel. In these studies, the mice learned the association of blue light CS and airpuff US with a rate similar to our observation 810,20,41,45,51 .…”
Section: Discussionsupporting
confidence: 82%
“…As mice appear to become distressed from restraint, this head-fixed preparation was developed to keep heads secure while reducing the amount of restraint required. While this preparation allows mice to ambulate on a cylindrical treadmill, others have also successfully collected behavioral data from head-fixed mice on a stable platform 24 .…”
Section: Discussionmentioning
confidence: 99%